Preparation and characterization of palm oil based polyalkyd films and composites with multi-walled carbon nanotubes - Muhammad Remanul, Islam (2015)
In this research, polyalkyd resins were prepared from palm oil by using polycondensation reaction. A two-step method viz., alcoholysis and esterification was conducted to synthesize polyalkyd resins. Prior to alcoholysis, crude palm oil was subjected for dehydration process to increase its unsaturation. Different types of catalysts such as, sulphuric acid, para-toluene sulfonic acid, phosphoric acid, sodium hydrogen sulphate and potassium hydrogen sulphate were used for the dehydration. In alcoholysis process, the triglyceride-based dehydrated oil was reacted with glycerol to produce monoglyceride. The prepared monoglyceride was further brought into contact with acid anhydride to prepare polyalkyds. Response surface methodology was used to optimize the reaction parameters for esterification like reaction temperature, reaction time, catalyst concentration, acid anhydride to mono-glyceride ratio and agitation speed. The optimum condition was used to prepare various types of polyalkyds by using different types of acid anhydrides such as, maleic anhydride, succinic anhydride, phthalic anhydride, 3,4,5,6-tetrahydrophthalic anhydride and cis-1,2-cyclohexanedicarboxylic anhydride. A comparison was drawn among the resins prepared by using different types and percentages of acid anhydrides. The produced bioresins were characterized for physico-chemical properties such as, viscosity, density, iodine value, acid value, drying time, non-volatile materials content, specific gravity, colour, etc. The resins prepared with optimum reaction parameters were subjected for curing process by using methyl ethyl ketone peroxide and cobalt naphthanate. To enhance the resinous property, multi-walled carbon nanotubes (MWCNTs) were dispersed into the resin at different percentages of loading such as, 0.5, 1.0 and 1.5 wt.%. The loading was optimized based on the tensile strength of the film. Finally, in-situ polymerization with carbon nanotubes during esterification was performed by adding optimum percentage of loading. The films produced from different formulations were characterized by different testing such as, adhesion, chemical resistivity, thermogravimetric analysis, differential scanning calorimetry, field-emission scanning electron microscopy, x-ray diffraction analysis, contact-angle measurement, tensile testing, pencil hardness, gloss, etc. In addition, the curing kinetics of the resin was analysed to evaluate the kinetic parameters such as, reaction rate, activation energy and degree of conversion in terms of time and temperature. Result analyses through RSM revealed a desirability of 0.985 for the reaction time of 88.64 min. Moreover, 91.5% fractional conversion was achieved actually, which is close to the predicted value. Analysis revealed that 3,4,5,6-tetrahydophthalic anhydride-based resin showed improved resinous property than others due to high degree of crosslinking. It was also found that higher amount of aliphatic acid anhydrides are responsible for high degree of crosslinking density, whereas higher thermal stability was ensured by the inclusion of aromatic acid anhydride. Finally, incorporation of MWCNTs into the alkyd resin enhanced the overall film properties, which was further improved through in-situ reaction. The physical bonding and mechanical entanglement were the possible reason for showing improved properties, as revealed from the analysis.